DO TAX STRUCTURES AFFECT INDONESIA ECONOMIC GROWTH? - Heru Iswahyudi (Faculty of Economics and Business, Universitas Gadjah Mada, 2018)
This paper investigates how changes in the tax structure may affect Indonesia’s long-run economic growth.* The growth effects of the mix of income taxes and consumption taxes are examined using a set of panel growth regressions, which account for indicators of the tax structure, as well as both the accumulation of physical capital and human capital. The results suggest that income taxes may not exert a statistically significant impact on long-run growth, while consumption taxes may have a positive and statistically significant impact. These results, however, are not robust to changes in the regression’s specifications. Hence, although previous studies predict that the mix of direct and indirect taxes may be an important determinant of long-run growth, this paper provides evidence that, in practice, this mix is unlikely to have an impact on the long-run economic growth of Indonesia. It is therefore suggested that policy makers could instead focus their attentions on directing tax reform in Indonesia toward improving tax administration and the equity of the tax system.